2019
DOI: 10.2478/johh-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Retarding contaminant migration through porous media using inclined barrier walls

Abstract: This study aims to assess the abilities of inclined barrier walls (BWs) to retard the migration of contaminants through porous media. Four cases of BW arrangements were considered, including a single inclined BW (BW1) and two adjacent BWs (BW1 and BW2) with different combinations of inclination ratios (i.e., I1 = θ1 /90° and I2 = θ2 /90°). Furthermore, the effect of the distance (L) between the contamination source and BW1 on the migration time (T) was evaluated. A numerical model (GeoStudio) containing two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consequently, the ADWR process at the DRPS operates in the absence of assignable causes and is "in control and capable" of producing water with respect to all examined WQPs except for the TN. This exception occurs because out of the 1000 samples, approximately 220 are expected to violate the These results support the fact that many agricultural drains in Egypt receive significant polluted agricultural and sewage effluents (Allam et al, 2019). Figure 6 presents the non-parametric process capability charts for COD as an example of the nonparametric process capability analysis performed on nonnormal WQPs.…”
Section: Parametric Process Capability For Delengat Pump Stationmentioning
confidence: 55%
See 1 more Smart Citation
“…Consequently, the ADWR process at the DRPS operates in the absence of assignable causes and is "in control and capable" of producing water with respect to all examined WQPs except for the TN. This exception occurs because out of the 1000 samples, approximately 220 are expected to violate the These results support the fact that many agricultural drains in Egypt receive significant polluted agricultural and sewage effluents (Allam et al, 2019). Figure 6 presents the non-parametric process capability charts for COD as an example of the nonparametric process capability analysis performed on nonnormal WQPs.…”
Section: Parametric Process Capability For Delengat Pump Stationmentioning
confidence: 55%
“…Unfortunately, this option has experienced significant challenges in sustaining, rather than improving, the current reuse level (MWRI, 2008). Undoubtedly, the drainage water reuse processes accompanied by many of challenges, but the most important and complex challenge is the significant amount of non-point source pollution received by the Egyptian irrigation and drainage network (Allam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that 222Rn transport can be properly modelled using open-source software tools MODFLOW-NWT and MT3D-USGS to minimize the uncertainty caused by sediment heterogeneity in transport times and increase the accuracy of transport time predictions. Allam [5] studied the effect of inclined barrier walls on the migration of contaminants across porous media. The results showed that the transport time was strongly affected by the inclination ratios of the barrier walls.…”
Section: Introductionmentioning
confidence: 99%
“…Despite potential threats of flash floods, they are resources of fresh water and clean energy. The freshwater could be stored in surface lakes or directed to increase groundwater storage and levels, retarding seawater intrusion process without physical barriers, [22,23]. Furthermore, the potential energy of flowing water could be converted to carbon-free electricity through hydropower facilities.…”
Section: Introductionmentioning
confidence: 99%